Diseño y evaluación de un equipo de prensado con tornillo sinfín, para extracción de lípidos a nivel de laboratorio para su aplicación en investigación científica. - Pilozo Vera, Steven Moisés (2016)
The present research aims to evaluate the extraction of chontilla (bactris gacipaes) in cold, to obtain virgin oil, in order to replace the consumption of conventional oils (African palm) by others produced by the region 's own seeds. It was used 3 kg of red Chontilla pulp from the coast zone which were distributed in 250 gr for each treatment and repetitions. In the development of the equipment the different alternatives were selected to facilitate the extraction, in addition, different velocities in rpm and several passes of the same sample were evaluated. The system was obtained with the extraction by means of a worm, to optimize the extraction process. The extractions and analysis of PH and wet performance were carried out in the Laboratory of Bromatology of the Technical University of Quevedo. The lipid profile analysis of the obtained oil was performed to each of the treatments and their repetitions. The results of the different proposed variables were calculated using the statistical package STATGRAPHICS for the determination of differences between treatments. In addition, the TUKEY test (p <0.05) was used to determine the difference between the means of the levels. What I carry in this way to the respective conclusions and recommendations deliberated by the objectives set out in this investigative work.